Acute Lower Leg Compartment Syndrome: A Rare Complication following CABG. (21st July 2016) - Tahir, Muazzam; Galvin, Sean
Abstract : Compartment syndrome of lower legs following coronary artery bypass grafting is a rare complication which results from a combination of local and systemic factors. Early recognition is vital for good outcome. The case discussed describes this rare complication of CABG resulting in long term disability.